An appraisal of online audio Qur'an as a new media tool for civilization - Abubakar, Adamu; Zeki, Akram M.; Hisham, Akmal (nstitute of Electrical and Electronics Engineers Inc., 2016)
In this paper we evaluate online audio Qur’an capability as a new media tool. The fact that the number of audio Qur’an on the Internet is increasing, raised a question on whether it could be used as a new media tool to incorporate both Islamic teaching and civilization. Audio Qur’an is a resource that will impact people in many ways. In the circumstances where people that cannot be able to read text Qur’an which is mostly in Arabic, listening it in audio and following is a good starting step of learning. Those people could also gain from some additional information that the sources of this online audio Qur’an might introduce. This study uses quantitative survey research methodology and investigates how online audio Qur'an could be use as a new media tool for civilization. The research findings indicate that “Educational level” and “Using audio Qur’an” exerted a huge impact on positive perception of incorporation of civilization to understanding of Qur'an. However, the effect of accuracy and trust on the sources of such integration could raise serious questions and can be perceived differently, whereas the benefit is enormous.